Public Transport and the Decline of the Traditional Retail Sector in South Africa - Ruhiiga, Tabukeli M. (Journal of Human Ecology, 2012)
This paper reports the results of an investigation of the impact of recent developments in public transport on the traditional retail sector. Data collection was carried out based on four towns in the Eastern Cape Province selected on the basis of having a significant consumer market. For each of these centres, three localities located in 25-35-45kilometre radii were selected and in each of these, a random sample of 50 households was interviewed about their income distribution, shopping patterns, patronage of retail outlets and access to public transport. The data was analysed using frequency distributions and correlation. The findings indicate that access to public transport plays an indirect but critical role in the shopping patterns of households. The decline of the traditional retail sector has been facilitated by developments in transport and changing consumption trends at local, regional and global scales.
Keywords: Household Shopping Patterns; Trip Frequencies; Passenger Transport; Economic Growth